Bidirectional crosstalk between the epithelial-mesenchymal transition and immunotherapy: A bibliometric study - Wei Du; Zemin Tang; Ashuai Du; Qinglong Yang; Rong Xu (Taylor & Francis Group, 2024)
Immunotherapy has recently attracted considerable attention. However, currently, a thorough analysis of the trends associated with the epithelial-mesenchymal transition (EMT) and immunotherapy is lacking. In this study, we used bibliometric tools to provide a comprehensive overview of the progress in EMT-immunotherapy research. A total of 1,302 articles related to EMT and immunotherapy were retrieved from the Web of Science Core Collection (WOSCC). The analysis indicated that in terms of the volume of research, China was the most productive country (49.07%, 639), followed by the United States (16.89%, 220) and Italy (3.6%, 47). The United States was the most influential country according to the frequency of citations and citation burstiness. The results also suggested that Frontiers in Immunotherapy can be considered as the most influential journal with respect to the number of articles and impact factors. "Immune infiltration," "bioinformatics analysis," "traditional Chinese medicine," "gene signature," and "ferroptosis" were found to be emerging keywords in EMT-immunotherapy research. These findings point to potential new directions that can deepen our understanding of the mechanisms underlying the combined effects of immunotherapy and EMT and help develop strategies for improving immunotherapy.